Training for change: A facilitator’s guide to gender-inclusive financial literacy and land rights - Abdykadyrova, Buazhar (2024)
This interactive and practical training facilitates adult learning and aims to build capacities to apply the concepts learned in everyday life. For example, it includes interactive roleplaying games, scenarios, and guest speakers who share their experiences to model sound financial behaviors.